Controlling the dynamics of Diabetes Mellitus with mathematical model - Adeyemo*, K.A.; Lawal†, T.A.; Azeez‡, I.A.; Philemon§, E.; Falade**, K.I.; Nwachukwu††, F.C.; Omame‡‡, A.; Lasisi§§, N. O.; Aye***, P.O. (International Journal of Mathematical Analysis and Modelling, 2025)
control parameters, was formulated. The obtained equilibrium point shows that there is no disease free equilibrium (DFE) but endemic equilibrium point (EEP) of the model, The Analysis of the model shows that the endemic equilibrium point of the model is both locally asymptotically stable (LAS) and globally asymptotically stable (GAS). Homotopy perturbation method was used to obtain the model solution. Nigeria diabetes values and parameters are used to obtain the sensitivity analysis of the sensitive parameters, and graphical simulations of the numerical solution of the state variables. The study provides a comprehensive guidance for the prevention and control of Type 1, Type 2 and gestational diabetes.